Internal Control Pemerintah Desa Dalam Pengelolaan Dana Desa - Retno Murni Sari (JRAK: Journal of Accounting Research and Computerized Accounting, 2020)
In order to achieve a state that is clean and free from corruption, it is necessary to have a commitment from the government by building a Government Internal Control System (SPIP) as in order to achieve effective, efficient, transparent and accountable management of state finances, it is mandatory to control the implementation of government activities. The need to apply the principles of accountability for village fund reporting and transparency is expected to result in compliance in the village government in managing village funds starting from the planning and budgeting stages. Because so far the management of village funds is not in accordance with the provisions set by the government. This study aims to analyze the internal control of the village government in the management of the 2018 Village Fund by taking the Pojok Village Government, Ngantru District, Tulungagung Regency, East Java. The data used are primary data obtained directly from the source by means of observation and structured interviews with Pojok Village Government Officials (Village Head, Head of Finance, Head of Development, and BPD). Secondary data obtained from third parties or literature, documentation, reference books, laws, and electronic media. The data analysis method used in this research is descriptive with a qualitative approach. The results show that the implementation of the Government Internal Control System in the management of the Village Fund and the implementation of village development has been carried out in accordance with applicable regulations, implemented with openness and accountability, and invites local village communities to participate in village development using the 2018 Village Fund.